French enterprise zone program: did it help the residents of deprived neighborhoods? - Pauline Charnoz (European Regional Science Association (ERSA), 2014)
This paper evaluates the effect of the French enterprise zone program on residents of these deprived neighborhoods. A second contribution is the evaluation of the composition effects in the zones and of externalities on the neighbors of the enterprise zones. The third contribution is the evaluation of a specific feature : the local hiring condition. It shows that there are a significant decreasing effect of the program on unemployment of residents and some small negative externalities on neighboring areas. There is also evidence of composition effects. There is thus two channels for the effect of the program on residents~: residents already there before designation (or that would have been there in absence of the program) got more jobs but the program also helps to attract or retain residents with better labor market outcomes. Moreover, the results suggest that the local hiring condition is working.
Keywords: R10; J00; R58; 330